Household food security and WASH practices in children with undernutrition: a case study in low middle income area in Semarang, Indonesia - Anggraheny, Hema Dewi; Setiawan, M. Riza; Widiasih, Esti; Dewi, Ernanda Candra (BKM Public Health and Community Medicine, 2024)
Purpose: This study analyzed the correlation between household food security (HFS) and WASH practices toward nutritional status in children with undernutrition. Methods: This type of research was analytically observational with a cross-sectional design. The sample in this study was 55 mothers with children with a history of undernutrition aged 6 to 23 months. The Rank Spearman test was conducted to analyze this study. Results: The prevalence of stunted and severely stunted was 34.55%, respectively; underweight and severely underweight were 36.36%, respectively; and wasted and severely wasted were 30.91 and 16.36% respectively. The percentage of respondents with mild, moderate, and severe food insecurity were 23.6, 7.3, and 12.7% respectively. The average value of WASH practices was rated as good among all respondents. Household food security score was associated with WAZ (p=0.008 and r=0.352) and HAZ (p=0.027 and r=0.299) but was not associated with WHZ (p=0.067; r=0.248). WASH practice was associated with WAZ (p=0.000; r=0.504), HAZ (p=0.000; r=0.455), and WHZ (p=0.000; r=0.334). Conclusion: There were still conditions of severe food insecurity and undernutrition problems that need the focus of attention. There is a need for monitoring by looking at certain aspects, such as HFS and WASH practices in reducing undernutrition.